2010
DOI: 10.1115/1.4002502
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Worn Hybrid Journal Bearing System With Different Recess Shapes Under Turbulent Regime

Abstract: The objective of the present paper is to study analytically the influence of wear on the performance of a capillary-compensated, four-pocket, hybrid journal bearing system operating in a turbulent regime by considering various geometric shapes of recess. The present study deals with bearings having four different geometric shapes of recess, i.e., square, circular, elliptical, and triangular recessed bearings. The wear on the bearing surface is modeled using Dufrane’s abrasive wear model. The Reynolds equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Most of the texture shapes exhibit similar trend of improvement in performance parameters up to a certain value of aspect ratio and then start decreasing with further increase in the aspect ratio. As far as more improvement in (14) Variation in load support (% )=w Turbulent −w Laminar w Laminar × 100…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the texture shapes exhibit similar trend of improvement in performance parameters up to a certain value of aspect ratio and then start decreasing with further increase in the aspect ratio. As far as more improvement in (14) Variation in load support (% )=w Turbulent −w Laminar w Laminar × 100…”
Section: Theorymentioning
confidence: 99%
“…They observed that performance parameters may vary depending on the tilting angle and radial adjustments. Nicodemus and Sharma [14] analytically investigated the effect of wear and recess shape on capillary compensated, four-pocket, hybrid journal bearing system running in turbulent regime. Dufrane's abrasive wear model (1983) and Constantinescu's model were used to incorporate wear and turbulent conditions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al 3 studied the influence of geometric shape of recess on the performance of a flexible hybrid journal bearing system. Very recently, Nicodemus and Sharma 4 investigated the effect of geometric shape in conjunction with the effect of wear on the performance of hybrid journal bearing operating in turbulent regime. They extended their research work to investigate the influence of geometric shape of recess on the performance of an orifice-compensated hydrostatic/hybrid journal bearing operating with micropolar lubricant.…”
Section: Introductionmentioning
confidence: 99%
“…They extended their research work to investigate the influence of geometric shape of recess on the performance of an orifice-compensated hydrostatic/hybrid journal bearing operating with micropolar lubricant. 5 The studies [1][2][3][4][5] reveal that proper selection of the geometric shape of recess is very important to obtain the desired performance of bearing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation